Procesos didácticos de la indagación y el aprendizaje de la ciencia y tecnología en niños de la institución educativa inicial N°500 Ramón Castilla 2024 - Yance Ruiz, Flor de Rosa (2025)
The objective of this research is to determine how the level of application of the inquiry didactic processes is related to the level of learning in science and technology among the children of the Initial Educational Institution No. 500 Ramón Castilla in 2024. This study adopts a quantitative relational approach, with a non experimental, correlational and cross-sectional design. The sample is composed of all the children of the institution, totaling 41 participants. For data collection, the observation technique was used, using an observation guide validated by three experts in the area. The reliability of the guide was evaluated using the item correlation method, using the Cronbach Alpha coefficient after conducting a pilot test. The results indicated a correlation coefficient (Spearman's Rho = 0.815), which reflects a high positive correlation between the variables studied. This suggests that an adequate application of the inquiry didactic processes is associated with a better level of learning in science and technology. With a bilateral significance value of 0.05, the correlation found is statistically significant, highlighting the importance of applying effective teaching strategies to improve learning in these areas.